2008
DOI: 10.4067/s0717-95022008000400027
|View full text |Cite
|
Sign up to set email alerts
|

Detección Molecular de Estreptococos Cariogénicos en Saliva

Abstract: RESUMEN:Streptococcus mutans y Streptococcus sobrinus han sido indicados como los principales agentes etiológicos de la caries dental. Sin embargo, los métodos microbiológicos y bioquímicos, disponibles actualmente en Chile, no permiten la rápida detección e identificación de estas bacterias. El objetivo de este trabajo fue implementar la metodología de reacción en cadena de la polimerasa (PCR) para detectar la presencia de S. mutans y S. sobrinus en saliva. Participaron de este estudio 51 escolares (5 a 17 añ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…S. mutans and S. sobrinus were clinical samples obtained from children of La Araucanía Region isolated in a previous study and confirmed by PCR-RFLP ( Salazar et al , 2008 ).…”
Section: Methodsmentioning
confidence: 71%
“…S. mutans and S. sobrinus were clinical samples obtained from children of La Araucanía Region isolated in a previous study and confirmed by PCR-RFLP ( Salazar et al , 2008 ).…”
Section: Methodsmentioning
confidence: 71%
“…Clinical isolates of Streptococcus mutans were obtained from the bacterial strain collection of our research center and confirmed by PCR as previously described [ 18 ]. Bacteria were grown on Columbia agar plates supplied with sucrose (1%) and incubated in anaerobic atmosphere (Anaerobic Generator GasPak EZ, Becton, Dickinson and Co., NY, USA) at 37°C and for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using saliva as a source of cariogenic bacteria show that the presence of the microorganisms studied from the mutans group was at 100% 13 . Given that the intention of the studies is to relate the presence of cariogenic bacteria and dental caries to confirm risk in subsequent analytical studies, using saliva as a source of the bacteria studied does not permit establishing an effective association.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated based on the historical tendency 12,13 from the studies with most similarity with the procedures used in this study. The participants were selected according to the following criteria: children aged between three and five years, residing in the geographical area of the target population of study, officially registered in foster homes of the region, and that parents accepted to participate in the study by signing an informed consent.…”
Section: Methodsmentioning
confidence: 99%